2014
DOI: 10.3168/jds.2013-6984
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profiles, meat quality, and sensory attributes of organic versus conventional dairy beef steers

Abstract: Meat from Holstein and crossbred organic and conventional dairy steers were evaluated and compared for fatty acid profiles, meat quality, sensory attributes, and consumer acceptance. Bull calves (n=49) were randomly assigned to 1 of 3 replicated groups: conventional (CONV), organic (ORG, pasture + concentrate), or grass-fed organic (GRS) and were born at the University of Minnesota West Central Research and Outreach Center (Morris, MN) between March and May 2011. The CONV steers (n=16) were fed a diet that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
(26 reference statements)
0
28
2
Order By: Relevance
“…Fatty acid composition is one of the most important indicator for meat nutritional value and closely relates to meat flavor and human health (Bjorklund, Heins, Dicostanzo, & Chester‐Jones, 2014; Seppänen‐Laakso, Laakso, & Hiltunen, 2002). In current study, 18 fatty acid contents along with the levels of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) were analyzed in the control and processed samples to indicate meat nutritional conditions after different thermal processing (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid composition is one of the most important indicator for meat nutritional value and closely relates to meat flavor and human health (Bjorklund, Heins, Dicostanzo, & Chester‐Jones, 2014; Seppänen‐Laakso, Laakso, & Hiltunen, 2002). In current study, 18 fatty acid contents along with the levels of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA) were analyzed in the control and processed samples to indicate meat nutritional conditions after different thermal processing (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed lower consumer acceptance of grass-fed beef compared to beef raised on concentrate (Bjorklund et al , 2014; Hunt et al , 2014; Legako et al , 2015; Maughan et al , 2012). Most comparisons are typically between very low fat grass-fed beef with much higher fat grain-fed produce (Van Elswyk and McNeill, 2014).…”
Section: Opportunities For Improving Meat Qualitymentioning
confidence: 92%
“…Beef can be a good source of mono-unsaturated oleic acid as well as short and long chain omega-3 fatty acids, with proven health benefits. Ruminants also produce a number of unique unsaturated fatty acids (vaccenic and rumenic) which probably have positive human health effects (Bjorklund et al , 2014; Daley et al , 2010; Pavan and Duckett, 2013). Importantly, unsaturated fat has been shown to significantly increase satiety compared to saturated fats (Maljaars et al , 2009).…”
Section: Opportunities For Improving Meat Qualitymentioning
confidence: 99%
“…However, the majority of sensory research on grass‐fed beef has only explored one or two biological types at a time. These include traditional beef breeds: Angus (O'Quinn et al., ), Wagyu (Frank, Joo, & Warner, ), Hereford (Realini, Duckett, Brito, Dalla Rizza, & De Mattos, ), and Simmental (Nuernberg et al., ); crossbreeds (Torrico et al., ); and some dairy cattle such as Holstein (Bjorklund, Heins, DiCostanzo, & Chester‐Jones, ). These studies come from all over the world, but there is very little current research examining acceptability of grass‐fed beef from different biological types in the United States.…”
Section: Introductionmentioning
confidence: 99%